The Gene bldA, a Regulator of Morphological Differentiation and Antibiotic Production in Streptomyces - Stefanie Hackl; Andreas Bechthold (2015)
Streptomyces species are well known for their particular features of morphological differentiation. On solid agar, a mold‐like aerial mycelium is formed and spores are produced, in which the bld genes play a crucial role. In S. coelicolor , mutations in one specific bld gene called bldA led to a “naked” phenotype lacking aerial hyphae and spores. This peculiar behavior became a major interest for scientific research in the past and it was revealed that bldA is coding for a unique tRNA able to translate a UUA codon into the amino acid leucine. UUA codons are a very rare property of G + C‐rich Streptomyces genomes. The impact of bldA on morphology can in parts be attributed to the regulatory effect of bldA on the translational level, because TTA‐containing genes can only be translated into their corresponding protein in the presence of a fully functioning bldA gene. In addition to the visible effect of bldA expression on the phenotype of S. coelicolor , bldA mutants were also deficient in antibiotic production. This led to the assumption that the role of bldA must exceed translational control. Many TTA‐containing genes are coding for transcriptional regulators which are activating or repressing the transcription of many more genes. Proteomics and transcriptomics are two powerful methods for identifying bldA target genes and it was possible to assign also post‐translational regulation to bldA . This review wants to give a short overview on the importance of bldA as a regulator of morphological differentiation and antibiotic production by switching on “silent” gene clusters in Streptomyces .